Inspiratory and Lower-Limb Strength Importance in Mountain Ultramarathon Running. Sex Differences and Relationship with Performance - Ignacio Martinez-Navarro; Antonio Montoya-Vieco; Eladio Collado; Bárbara Hernando; Carlos Hernando (MDPI AG, 2020)
The study was aimed at comparing lower-limb strength and respiratory parameters between male and female athletes and their interaction with performance in a 107 km mountain ultramarathon. Forty seven runners (29 males and 18 females; mean ± SD age: 41 ± 5 years) were enrolled. Lower-limb strength assessment comprised a squat jump test, an ankle rebound test, and an isometric strength test. Respiratory assessment included pulmonary function testing and the measurement of maximal inspiratory pressure. Male athletes performed largely better in the squat jump (26 ± 4 vs. 21 ± 3 cm; p < 0.001; d = 1.48), while no sex differences were found in the other two lower-limb tests. Concerning the respiratory parameters, male athletes showed largely greater values in pulmonary expiratory variables: forced vital capacity (5.19 ± 0.68 vs. 3.65 ± 0.52 L; p < 0.001; d = 2.53), forced expiratory volume in 1 s (4.24 ± 0.54 vs. 2.97 ± 0.39 L; p < 0.001; d = 2.69), peak expiratory flow (9.9 ± 1.56 vs. 5.89 ± 1.39 L/min; p < 0.001; d = 2.77) and maximum voluntary ventilation in 12 s (171 ± 39 vs. 108 ± 23 L/min; p < 0.001; d = 1.93); while no sex differences were identified in maximal inspiratory pressure. Race time was associated with ankle rebound test performance (r = −0.390; p = 0.027), isometric strength test performance (r = −0.349; p = 0.049) and maximal inspiratory pressure (r = −0.544; p < 0.001). Consequently, it seems that athletes competing in mountain ultramarathons may benefit from improving lower-limb isometric strength, ankle reactive strength and inspiratory muscle strength. Nevertheless, further interventional studies are required to confirm these exploratory results. In addition, the fact that the magnitude of the sex difference for isometric strength was minor, as compared with the other strength tests, could represent one of the factors explaining why the performance gap between males and females is reduced in ultramarathons.